Development of a comprehensive sustainability index for extractive and mining companies: Integrating the Sustainable Development Goals - Marta Fernández-Hernández; Pedro Mora; Marcelo F. Ortega; Juan Pous Cabello (Heliyon)
Sustainability in the extractive and mining industry has become a key global concern, necessitating alignment with the United Nations Sustainable Development Goals (SDGs). This research introduces an innovative, scientific index-based assessment methodology designed to quantify the contribution of companies in these sectors to the SDGs. The methodology leverages a metric index scoring system to evaluate and enhance their sustainability performance.The methodology involves scoring a series of parameters associated with each SDG, resulting in individual indices that are rescaled for comparability. This comprehensive approach also integrates environmental, social, and economic factors. The practical application of this index is critical, providing a step-by-step guide for extractive and mining companies to adopt and utilize the sustainability index, aiding in compliance with future regulations.The results of this study show that the system of SDGs, targets, aspects, and metrics is naturally weighted towards social issues. It has also been observed that the SDG system, with respect to the targets, is not balanced. This same heterogeneous behavior occurs for aspects. This implies that the system is naturally weighted, which directly affects the comparison of contribution. The proposed methodology provides a process of normalization of indices that avoids this natural weighting, allowing the comparison of results.This study advances a comprehensive methodology for evaluating extractive companies' contributions to the SDGs, incorporating multiple dimensions and expert opinions, and its adaptability allows for continuous improvement by incorporating new parameters. The Susceptibility Index helps management assess contributions on a scale of 0–10, facilitating ongoing improvements and anticipating regulatory changes.This research enhances the assessment of extractive companies' SDG performance, promoting responsible practices. The open-access nature of the methodology enables any organization to conduct a sustainability analysis, fostering transparency and collaboration.